Immunological Profiles, Oxidative Stress Biomarkers and Plasma Cholinesterase Activities in Patients with Immune-Mediated Inflammatory Diseases Treated in a Clinic in Duhok, Iraq - Abdullah R.; Mohammad F.; Eassa S. (Acta Medica Bulgarica)
The purpose of the present study was to measure the levels of selected plasma biochemical variables among cases of immune-mediated inflammatory diseases (IMIDs), other than rheumatoid arthritis, treated in a clinic in the city of Duhok, Iraq, since such information is scarce in the region.